Photoactivation of the BLUF Protein PixD Probed by the Site-Specific Incorporation of Fluorotyrosine Residues - Gil, Agnieszka A; Laptenok, Sergey P; Iuliano, James N; Lukacs, Andras; Verma, Anil; Hall, Christopher R; Yoon, Grace E; Brust, Richard; Greetham, Gregory M; Towrie, Michael; French, Jarrod B; Meech, Stephen R; et al. (Journal of the American Chemical Society, 2017)
The flavin chromophore in blue-light-using FAD (BLUF) photoreceptors is surrounded by a hydrogen bond network that senses and responds to changes in the electronic structure of the flavin on the ultrafast time scale. The hydrogen bond network includes a strictly conserved Tyr residue, and previously we explored the role of this residue, Y21, in the photoactivation mechanism of the BLUF protein AppA by the introduction of fluorotyrosine (F-Tyr) analogues that modulated the pK and reduction potential of Y21 by 3.5 pH units and 200 mV, respectively. Although little impact on the forward (dark- to light-adapted form) photoreaction was observed, the change in Y21 pK led to a 4000-fold increase in the rate of dark-state recovery. In the present work we have extended these studies to the BLUF protein PixD, where, in contrast to AppA , modulation in the Tyr (Y8) pK has a profound impact on the forward photoreaction. In particular, a decrease in Y8 pK by 2 or more pH units prevents formation of a stable light state, consistent with a photoactivation mechanism that involves proton transfer or proton-coupled electron transfer from Y8 to the electronically excited FAD. Conversely, the effect of pK on the rate of dark recovery is markedly reduced in PixD. These observations highlight very significant differences between the photocycles of PixD and AppA , despite their sharing highly conserved FAD binding architectures.